2020
DOI: 10.1039/d0ta07708a
|View full text |Cite
|
Sign up to set email alerts
|

A trifluoromethyl-grafted ultra-stable fluorescent covalent organic framework for adsorption and detection of pesticides

Abstract: A fluorine-rich ultra-stable fluorescent covalent organic framework for adsorption and detection of pesticides was designed and prepared via the Povarov reaction in a flask.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 61 publications
0
45
0
Order By: Relevance
“…COF−Ph was obtained according to previous work [3b] and characterized as shown in the Supporting Information. Cobalt complex of COF−Ph was used to contrast with counterpart of COF‐Pyr in order to explore the active sites of electrocatalysts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…COF−Ph was obtained according to previous work [3b] and characterized as shown in the Supporting Information. Cobalt complex of COF−Ph was used to contrast with counterpart of COF‐Pyr in order to explore the active sites of electrocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The data shown in the N 1s X‐ray photoelectron spectroscopy (XPS) spectra were consistent with these conclusions. In Figure S5, the N 1s XPS peak of COF‐Pyr was apparently broader than that of TPB‐DMTP‐COF; the spectra of COF‐Pyr showed three peaks at 399.8, 399.5, and 400.4 eV, representing imine, [13] quinoline, [3b] and pyrimidine, respectively. It was shown that imine bonds were partially converted to quinoline units via the Povarov reaction, and the pyrimidine functional groups were successfully introduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19,101] COFs and MOFs are materials with interesting properties and aspects such as their porosity, possibility of modification, regulated functionalization, and designable topologies. [19,[99][100][101] In literature, there are reported investigations where they use magnetic nanocomposites, Fe3@SiO 2 @UiO-67 and MOF-Fe 4 O 3 -GO-β-cyclodextrin, for the removal of glyphosate, timethoxan, imidacloprid, acetamiprid, dinotefuran, clothianidin, and nitenpyram from aqueous systems. [102,103] Wang et al ( 2020) reported the utilization of ZIF-8@MWCT for adsorption of inorganic pesticides from contaminated waters.…”
Section: Nanostructured Bio-polymeric Hybrid Materials Used In Aqueous Pesticide Removalmentioning
confidence: 99%
“…Pesticides consist of a set of insecticides and herbicides, primarily applied in forestry and crop plantations. In the case of chlorothalonil (CTL), nitrofen (NF), trifluralin (TFL), and dicloran (DCN), these carcinogens accumulate easily in the body, resulting in acute concentrations that cause cancers in humans and livestock [ 2 ]. Therefore, various detection methods are being investigated, including capillary electrophoresis [ 3 , 4 ], liquid chromatography [ 5 , 6 ], and electrochemical methods [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%